1992
DOI: 10.1017/s0081305200026066
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Farmers Forward Contract In Factor Markets?

Abstract: This study investigated farmers' incentive to forward purchase inputs. A model of farmer decision making was used to derive an optimal forward contracting rule. Explicit in the model was the tradeoff between the quantity of input to be purchased in advance, and the remaining portion to be purchased later on the spot market. Results indicated that the primary reasons farmers contract inputs are to reduce risk and to speculate on favorable price moves. A numerical example of fertilizer used in corn production in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…These farms have specific input requirements and tend to have higher production costs (Uematsu and Mishra, ) and using methods to reduce input costs, may help the bottom line of these farms. Additionally, Haydu et al () found that the reasons that farmers contract for inputs are the reduction of risk and speculation on favorable price moves.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These farms have specific input requirements and tend to have higher production costs (Uematsu and Mishra, ) and using methods to reduce input costs, may help the bottom line of these farms. Additionally, Haydu et al () found that the reasons that farmers contract for inputs are the reduction of risk and speculation on favorable price moves.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it has been pointed out in the literature that farmers can mitigate the effects of risk by forward contracting, a form of input management strategy, in input markets (Mishra and Morehart, ). Forward contracting inputs could aid planning and allow farmers to diversify purchases over time (Haydu et al, ). Finally, input contracting was found to significantly affect financial returns to dairy farmers in the United States (Mishra and Morehart, ).…”
Section: Marketing and Management Skillsmentioning
confidence: 99%
“…Generally, in land as well as labor and capital markets, sunk costs associated with advance production (and their resulting risks and incentives) are not relevant. Forward contracting also occurs in agricultural input supply markets (Haydu, Myers, and Thompson, 1992;Mishra and Perry, 1999). Additionally, forward delivery is a standard ''simplest'' market design in experimental markets (Phillips, Menkhaus, and Krogmeier, 2001).…”
mentioning
confidence: 99%
“…This study addresses the profit impacts of adoption, but risk management tools -as the name implies -are designed to limit risk exposure. Our analysis focuses on the profit motivation due to evidence provided by several previous studies that indicate that farm operators are principally concerned with the profit enhancing properties of risk management tools (Pennings et al, 2004;Haydu et al, 1992;Patrick et al, 1998). This notion is derived from surveys of farm operators and extension workshop participants.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Pennings et al (2004) find that farmers subscribe to market advisory services based on their price-enhancing characteristics rather than their risk-reducing features. Haydu et al (1992) show that, with respect to forward-contracting fertilizer purchases, farmers are primarily motivated by price discounts, not risk aversion or hedging potential. Patrick et al (1998) find that large-scale Midwestern grain producers think of marketing tools as ways of enhancing profits rather than as ways of managing price risk.…”
Section: Introductionmentioning
confidence: 91%